2003
DOI: 10.1104/pp.103.023556
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Crystal Matrix Protein Associated with Calcium Oxalate Precipitation in Vacuoles of Specialized Cells

Abstract: The formation of calcium (Ca) oxalate crystals is considered to be a high-capacity mechanism for regulating Ca in many plants. Ca oxalate precipitation is not a stochastic process, suggesting the involvement of specific biochemical and cellular mechanisms. Microautoradiography of water lettuce (Pistia stratiotes) tissue exposed to 3 H-glutamate showed incorporation into developing crystals, indicating potential acidic proteins associated with the crystals. Dissolution of crystals leaves behind a crystal-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 53 publications
4
56
0
11
Order By: Relevance
“…In addition, not all amino acids in a mass of proteins exert a specialized function in biological fields. Furthermore, acidic amino acids were reported to be found within stones and it was hypothesized that they are involved in the formation of stones in specialized plant cells (2). Understanding the characteristics of amino acids in peptide or proteins might help in the understanding of how proteins are related to stone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, not all amino acids in a mass of proteins exert a specialized function in biological fields. Furthermore, acidic amino acids were reported to be found within stones and it was hypothesized that they are involved in the formation of stones in specialized plant cells (2). Understanding the characteristics of amino acids in peptide or proteins might help in the understanding of how proteins are related to stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that proteins are involved in the formation of calcium oxalate depositions in plants (2). Therefore, proteins that present in the stones or urine can be considered to modify crystal formation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many electron microscopic studies showing the crystal chambers and crystal-associated materials in the vacuoles of crystal idioblasts, little was known about their origin. Recently, Li et al (2003) reported that the matrix protein in calcium oxalate crystals was transported to the vacuoles via the Golgi apparatus. In Japanese yam, there were amorphous materials in the translucent parts of crystalloplastids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the diffraction pattern revealed that in the species studied there was only one mineral, 90% calcium as shown by EDXAR analysis, being the first report of the elemental composition of the core from aggregated crystals of weddellite. In vacuoles, which are environments rich in water and ionic solutions, the signal could be provided when different factors are present, such as a decrease in the oxalate-oxidase enzyme (Volk et al, 2002), an increase in the glycolate concentration (Yu et al, 2010), or the formation of a protein matrix (Li et al, 2003), as occurs in the other plants (Horner and Wagner, 1995). Some of these factors may contribute to the quick weddellite precipitation in Cephalocereus.…”
Section: Corementioning
confidence: 99%